Bond strength between blended slag and Class F fly ash geopolymer concrete with steel reinforcement. (June 2015) - Castel, Arnaud; Foster, Stephen J.
Abstract: In this paper, geopolymer concrete bond with both deformed and smooth reinforcing steel bars is investigated using the standard RILEM pull-out test. The geopolymer binder is composed of 85.2% of low calcium fly ash and 14.8% of ground granulated blast furnace slag (GGBFS). The tests were aimed to assess the development of the bond strength from 24 h to 28 days after casting, with different heat curing conditions. The results show that 48 h of heat curing at 80 °C is required in order to obtain similar or better performances to those of the reference 45 MPa OPC concrete. The 28-day bond strength and the overall bond stress–slip behaviour of the geopolymer concrete were similar to those previously reported for OPC-based concretes. Providing intensive heat curing, high early bond strength can be achieved showing that Class F fly ash geopolymer concrete is well suited for precast applications.